2006
DOI: 10.1080/09687860500473630
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the ATPase activity of the yeast mitochondrial ABC transporter Atm1p by thiol compounds

Abstract: The ATP binding cassette (ABC) transporter Atm1p of the mitochondrial inner membrane performs crucial roles in both the biogenesis of cytosolic/nuclear iron-sulfur proteins and cellular iron homeostasis. Since the function of the mitochondrial iron-sulfur cluster (ISC) assembly machinery is also required for these two processes, Atm1p is thought to translocate a still unknown product of this pathway to the cytosol. Here, we provide a detailed in vitro characterization of Atm1p in order to better understand its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 49 publications
(53 reference statements)
7
75
1
Order By: Relevance
“…However, other possibilities cannot be ruled out, for example that ATM3 transports multiple substrates, including the pterin precursor of Moco. In support of a sulfide derivative as substrate, it was shown that the ATPase activity of yeast Atm1p is stimulated by thiol compounds in vitro (Kuhnke et al, 2006). Although it has been suggested that ATM3 transports cadmium, our finding that cadmium has little effect on root length in atm3 mutants (Fig.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…However, other possibilities cannot be ruled out, for example that ATM3 transports multiple substrates, including the pterin precursor of Moco. In support of a sulfide derivative as substrate, it was shown that the ATPase activity of yeast Atm1p is stimulated by thiol compounds in vitro (Kuhnke et al, 2006). Although it has been suggested that ATM3 transports cadmium, our finding that cadmium has little effect on root length in atm3 mutants (Fig.…”
Section: Discussioncontrasting
confidence: 52%
“…Although ATM3, and therefore the substrate, is required for cytosolic Fe-S clusters, it is unlikely to be an Fe-S cluster. First, free Fe-S is unstable and would need to be liganded, for instance by a small peptide (Kuhnke et al, 2006). Second, iron does not accumulate in the mitochondria of atm3 mutants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ABC transporters use the binding and hydrolysis of ATP to power the movement of substrates. Surprisingly, many ABC transporters exhibit a basal ATPase activity in vitro in the absence of transport substrate, which is stimulated between 2-and 10-fold when a transport substrate is added (25)(26)(27). ABCB10 showed basal ATPase activity, with apparent kinetic parameters similar to those of other ABC transporters (28,29), when it was purified in DDM and either CHS or CDL, with or without reconstitution into liposomes (Table 1, Fig.…”
Section: Structure Abcb10 In Complex With Nucleotide Analogs and Withoutmentioning
confidence: 99%
“…If the mitochondrial pool of NFS1 provides a sulfur-containing precursor for the CIA pathway, then this needs to be exported to the cytosol via a transporter. A probable candidate is the ABC transporter of the mitochondria, Atm1 in yeast [14,15]. The orthologues in mammals (ABCB7) and plants (ATM3) are also required for the activity of cytosolic Fe-S enzymes [16][17][18].…”
Section: Introductionmentioning
confidence: 99%